A superação da tradição mimética em A Rainha dos Cárceres da Grécia, de Osman Lins - TANCREDO, Rogério Alan (Universidade Federal do Pará, 2023)
In the passage from the 19th to the 20th century, the contemporary narrative suffers a rupture caused by experiments on the works of authors such as Franz Kafka, Marcel Proust, James Joyce and Virginia Woolf. From then on, the novel will never be the same, because the narrative, rather than representing reality in its rich details, now brings to the surface the act of creation and the narrative’s own reality. This work consists in a research project that will say about the revision of the mimetic tradition in the book A Rainha dos Cárceres da Grécia (1976), written by Osman Lins, that focuses the process of writing of a novel dressed as an essay, that is to say, of a novel that focuses on itself; and it has as theoretical basis the thought of Giorgio Agamben with reference to contemporaneity and the Outside’s concept, by Maurice Blanchot, which can help to clarify and understand the transformations he has undergone, as well as the current position of the contemporary novel. For this, we will bring narrators who transformed and innovated the act of narrating to dialogue as the Lins’s narrator, who we believe has pointed to a new trend from the fusion of the romance genre with the essay genre, specifically in the book mentioned above, exploring the multiple possibilities of the creation and writing process.